2019
DOI: 10.1111/jphs.12297
|View full text |Cite
|
Sign up to set email alerts
|

Extent of extemporaneous compounding and pattern of prescribing and use of extemporaneous medicines in a developing setting

Abstract: Objectives To determine the extent of extemporaneous compounding, the prescribing pattern and use of extemporaneous medicines in a developing setting like Nigeria. Methods A cross‐sectional assessment was conducted at the Pharmacy Department of the premier teaching hospital in Nigeria. A pretested data collection form and direct inspection of packaging and labelling information were used for data extraction. Key findings About 100% (678) of the extemporaneous products were liquid dosage form made with triturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…[5][6][7][8] This time-honored practice is still ordered and remain a viable option by many practitioners. 9,10 A typical study indicated that a dermatologist prescribes 2 to 5 compounded medications daily. 11 Compounding can be defined as combining, admixing, diluting, reconstituting, or otherwise altering a drug or bulk drug substance to create a desired medication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] This time-honored practice is still ordered and remain a viable option by many practitioners. 9,10 A typical study indicated that a dermatologist prescribes 2 to 5 compounded medications daily. 11 Compounding can be defined as combining, admixing, diluting, reconstituting, or otherwise altering a drug or bulk drug substance to create a desired medication.…”
Section: Introductionmentioning
confidence: 99%
“… 5–8 This time-honored practice is still ordered and remain a viable option by many practitioners. 9 , 10 A typical study indicated that a dermatologist prescribes 2 to 5 compounded medications daily. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia, about 5% of 353 operating hospitals in the nation had dermatologic compounding facilities in the year 2020 (Selam & Ababu, 2021). In a study conducted at a teaching hospital in Nigeria, all the extemporaneous preparations were liquid dosage form prepared from crushed tablets, capsules and parenteral dosage forms (Yusuff, 2019). A study performed at Kenyatta hospital, Kenya to evaluate extemporaneously prepared products derived from oral solid dosage form alterations, a total of 392 oral liquid formulations were compounded over the study period of January, 2012 to December, 2013.…”
Section: Prevalence Of Extemporaneous Compoundingmentioning
confidence: 99%